Worksheet-based tools in Mathematics to improve the numeracy skills of grade 9 learners of Francisco P. Tolentino integrated high school - Amita, Carla Jean R. (b)
The study intended to analyze the significant difference between the before and after the implementation of worksheet-based tools in Mathematics. Type of research is quasi-experimental research design with the development model of ADDIE. The least mastered topics are probability, the volume of solid figures, operations on polynomials, slope and equation of a line, triangle similarity, and Pythagorean Theorem. The validity of worksheet-based tools on least mastered topics in Mathematics is achieved from three experts' validation of the expert sheet. According to the study's findings, the result presented that most of the pupils were in the "closely approximating mastery" category. This means that most learners need to focus on their understanding of the least mastered topics. The study revealed that many learners got 1 to 2 correct answers, indicating a common understanding of the topics. It was discovered that the data scores from the pretest results had improved after the suggested intervention. There is a significant difference in the level of numeracy of Grade 9 learners of the participating school before and after implementing worksheet-based tools in Mathematics. This may imply that the worksheet-based tool effectively improves learners' numeracy skills.
Master Thesis
Keywords: Mathematics; Numeracy; Least Mastered Topics; Worksheet